Measles: There is No Vaccine against Vaccine Phobia - McLaren, Rodney A., Jr.; Stein, Janet L.; Minkoff, Howard (American Journal of Perinatology, 2019)
In 2000, the United States had effectively eliminated endemic measles. Unfortunately, due to misinformation and non-scientific based concerns, the rate of measles vaccination has declined. The United States is in the midst of its largest outbreak of measles since 2014, with 1,095 confirmed cases as of June 2019. The reasons for the re-emergence of measles and what this epidemic illustrates about the anti-vaccine culture in the United States are explored in this article.
Keywords: health belief model; immunization; measles; measles–mumps–rubellaMMR vaccine; vaccination